Mitochondrial dysfunction reduces the activity of KIR2.1 K + channel in myoblasts via impaired oxidative phosphorylation - Woo, JooHan; Kim, Hyun Jong; Nam, Yu Ran; Kim, Yung Kyu; Lee, Eun Ju; Choi, Inho; Kim, Sung Joon; Lee, Wan; Nam, Joo Hyun (The Korean journal of physiology & pharmacology, 2018)
Myoblast fusion depends on mitochondrial integrity and intracellular Ca signaling regulated by various ion channels. In this study, we investigated the ionic currents associated with [Ca ] regulation in normal and mitochondrial DNA-depleted (ρ0) L6 myoblasts. The ρ0 myoblasts showed impaired myotube formation. The inwardly rectifying K current (I ) was largely decreased with reduced expression of KIR2.1, whereas the voltage-operated Ca channel and Ca -activated K channel currents were intact. Sustained inhibition of mitochondrial electron transport by antimycin A treatment (24 h) also decreased the I . The ρ0 myoblasts showed depolarized resting membrane potential and higher basal [Ca ] . Our results demonstrated the specific downregulation of I by dysfunctional mitochondria. The resultant depolarization and altered Ca signaling might be associated with impaired myoblast fusion in ρ0 myoblasts.